CEO Media Exposure & Cross-Sectional Stock Returns - Dankers, Bryce (My University, 2012)
This study looked at whether CEOs' media exposure affects their firm's security return when firms have good versus bad corporate merger and acquisition news.
Color poster with text and tables.
Keywords: Chief executive officers; Mass media--Influence; Corporate image; Corporations--Public relations; Stock exchanges and current events; Posters